HUBUNGAN POLA MAKAN DAN STRES TERHADAP KEKAMBUHAN GASTRITIS DI PUSKESMAS REJOSARI KOTA PEKANBARU - Ammelia, Selvi; Sari, Sabtria Winda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Gastritis is a disease or disorder in which the stomach wall is inflamed. This disorder is caused by excessive levels of hydrochloric acid (Hcl). The purpose of this study is to determine the relationship between diet and stress to the recurrence of gastritis in the Rejosari Health Center, Pekanbaru. This research was conducted at the Rejosari Health Center, Pekanbaru on December 23, 2024 – January 9, 2025. The sampling technique used the accidental sampling method, with a total of 97 respondents. The research design used is descriptive correlational with a cross sectional approach. The data collection tool is a questionnaire with analysis using the Chi-Square and Fisher's Exact Test with α = 0.05. The results of this study found that there was a relationship between diet and the recurrence of gastritis at the Rejosari Health Center, Pekanbaru with a P value of 0.001, and there was a relationship between stress and the recurrence of gastritis at the Rejosari Health Center, Pekanbaru with a P value of 0.000. The conclusion of this study is that there is a significant relationship between diet and stress on the recurrence of gastritis at the Rejosari Health Center, Pekanbaru. It is hoped that gastritis patients at the Rejosari Health Center in Pekanbaru City can manage their diet and manage stress to prevent gastritis and its recurrence. Keywords : Diet, Stress, Gastritis.